An open-ocean assessment of alkenone δD as a paleo-salinity proxy. (1st February 2019) - Gould, Jessica; Kienast, Markus; Dowd, Michael; Schefuß, Enno
Abstract: Sea surface salinity (SSS) is the least constrained major variable of the past (paleo) ocean but is fundamental in controlling the density of seawater and thus large-scale ocean circulation. The hydrogen isotopic composition (δD) of non-exchangeable hydrogen of algal lipids, specifically alkenones, has been proposed as a promising new proxy for paleo SSS. The δD of surface seawater is correlated with SSS, and laboratory culture studies have shown the δD of algal growth water to be reflected in the δD of alkenones. However, a large-scale field study testing the validity of this proxy is still lacking. Here we present the δD of open-ocean Atlantic and Pacific surface waters and coincident δD of alkenones sampled by underway filtration. Two transects of approximately 100° latitude in the Atlantic Ocean and more than 50° latitude in the western Pacific sample much of the range of open ocean salinities and seawater δD, and thus allow probing the relationship between δD of seawater and alkenones. Overall, the open ocean δD alkenone data correlate significantly with SSS, and also agree remarkably well with δD water vs δD alkenone regressions developed from culture studies. Subtle deviations from these regressions are discussed in the context of physiological factors as recorded in the carbon isotopic composition of alkenones. In a best-case scenario, the data presented here suggest that SSS variations as low as 1.2 can be reconstructed from alkenone δD.